Function of Succinoglycan Polysaccharide in Sinorhizobium meliloti Host Plant Invasion Depends on Succinylation, Not Molecular Weight - Hajeewaka C. Mendis (American Society for Microbiology, 2016)
ABSTRACT The acidic polysaccharide succinoglycan produced by the rhizobial symbiont Sinorhizobium meliloti 1021 is required for this bacterium to invade the host plant Medicago truncatula and establish a nitrogen-fixing symbiosis. S. meliloti mutants that cannot make succinoglycan cannot initiate invasion structures called infection threads in plant root hairs. S. meliloti exoH mutants that cannot succinylate succinoglycan are also unable to form infection threads, despite the fact that they make large quantities of succinoglycan. Succinoglycan produced by exoH mutants is refractory to cleavage by the glycanases encoded by exoK and exsH, and thus succinoglycan produced by exoH mutants is made only in the high-molecular-weight (HMW) form. One interpretation of the symbiotic defect of exoH mutants is that the low-molecular-weight (LMW) form of succinoglycan is required for infection thread formation. However, our data demonstrate that production of the HMW form of succinoglycan by S. meliloti 1021 is sufficient for invasion of the host M. truncatula and that the LMW form is not required. Here, we show that S. meliloti strains deficient in the exoK- and exsH-encoded glycanases invade M. truncatula and form a productive symbiosis, although they do this with somewhat less efficiency than the wild type. We have also characterized the polysaccharides produced by these double glycanase mutants and determined that they consist of only HMW succinoglycan and no detectable LMW succinoglycan. This demonstrates that LMW succinoglycan is not required for host invasion. These results suggest succinoglycan function is not dependent upon the presence of a small, readily diffusible form. IMPORTANCE Sinorhizobium meliloti is a bacterium that forms a beneficial symbiosis with legume host plants. S. meliloti and other rhizobia convert atmospheric nitrogen to ammonia, a nutrient source for the host plant. To establish the symbiosis, rhizobia must invade plant roots, supplying the proper signals to prevent a plant immune response during invasion. A polysaccharide, succinoglycan, produced by S. meliloti is required for successful invasion. Here, we show that the critical feature of succinoglycan that allows infection to proceed is the attachment of a “succinyl” chemical group and that the chain length of succinoglycan is much less important for its function. We also show that none of the short-chain versions of succinoglycan is produced in the absence of two chain-cleaving enzymes.